Pengaruh penggunaan model pembelajaran cooperative learning type team assisted individualiztion terhadap hasil belajar Matematika siswa kelas III Sekolah Dasar - Tuti Faoziah; Irfan Fajrul Falah (IKIP Siliwangi, 2026)
This Study aims to determine the effect of the cooperative learning model type TAI (Team Assisted Individualization) on the learning outcomes of third-grade students of SDN 1 Jalaksana. The type of research used is experimental research with the design used is Quasi-experimental and the design form is non-equivalent control group design. The instrument used in this study is a student learning outcome test (pre-test and post-test), the test used is an essay of 10 questions that have been tested for validity and reliability. The research sample taken is all third-grade students of SDN 1 Jalaksana. The average mathematics learning outcomes of third-grade students in the experimental class post-test are 85.86 and the control class post-test score is 71.89. Description of research data from post-test data analysis using the independent sample test shows a significance value of 0.000 <0.5. From the provision criteria if significance <0.5 then Ho is rejected Ha is accepted. Thus, it can be concluded that the implementation of the Team Assisted Individualization (TAI) learning model significantly influences mathematics learning outcomes in third-grade elementary school students. Keywords : Learning outcomes, Learning model, TAI.